Factors that Influence the Farming Business of Cocoa Farmers (Theobroma Cacao L) in Negeri Sepa, Amahei District, Central Maluku Regency - Louisa S. Manuhutu (Syntax Corporation Indonesia, 2023)
Plantations in Indonesia are dominated by smallholder plantations. This is a challenge as well as an opportunity for investors and farmers to develop their businesses and achieve greater added value from cocoa agribusiness. Negeri Sepa is located in a coastal area with the scope of village communities who mostly have a livelihood as farmers. Workers working in agriculture earn income that is used to make ends meet and improve household welfare. This study aims to determine the physical and non-physical factors of cocoa in Sepa Country, Amahai District, Central Maluku Regency. The method used in this study is quantitative descriptive to explain the Factors That Affect Cocoa Farmer Farming in Sepa Country. Data analysis in this study used a Frequency Table. The results of frequency tabulation show that the factors that affect cocoa farming in Sepa Country, Amahai District, Central Maluku Regency are Physical Factors (Climate, Soil & Topography) and Non-Physical Factors (Cocoa Farm Management, Capital, Number of Workers, Transportation, Marketing, Credit Facilities and Technology)